Cultivating mutual mentorship: Reimagining relational leadership in perioperative nursing - Dunn, Jennifer (Operating Room Nurses Association of Canada Journal, 2025)
The perioperative environment is one of the most complex in healthcare, requiring technical precision, interdisciplinary coordination, and the capacity for adaptive leadership. Traditional mentorship models, which are often hierarchical and episodic, no longer meet the evolving needs of today’s diverse surgical teams. This article presents a conceptual discussion of a Mutual Mentorship Model specifically designed for perioperative nursing. The model is informed by adult learning theory, transformational leadership, and Patricia Benner’s Novice to Expert framework, emphasizing reciprocity, psychological safety, and shared accountability through co-mentorship, where both participants engage as learners and contributors. The approach includes strategies such as cross-role matching, reflective dialogue, and mentorship cycles. These are supported by a set of modular resources currently in development. This paper outlines how they may eventually support integration within existing professional development systems. The model addresses skill development and the structural, emotional, and cultural challenges of perioperative work. In addition, a proposed evaluation plan is included to explore potential outcomes, such as increased clinical confidence, improved retention, and strengthened professional identity. By shifting mentorship from a transactional process to one centred on relationships and shared growth, this model offers a framework for fostering connection, leadership, and long-term resilience in perioperative nursing.